Artists and the Mind in the 21st Century - Koetsch, Geoffrey (Frontiers in Human Neuroscience, 2011)
In 2008, Lesley University Professors Geoffrey Koetsch and Ellen Schön conducted an informal survey of New England artists to ascertain the degree to which recent work in neuroscience had impacted the visual arts. The two curators mounted an exhibition (MINDmatters May-June, 2008) at the Laconia Gallery in Boston in which they showcased the work of artists who had chosen mental processes as their primary subject. These artists were reacting to the new vision of the mind revealed by science; their inquiry was subjective, sensory, and existential, not empirical. They approached consciousness from several vantage points. Some of the artists had had personal experience with pathologies of the brain such as dementia or cancer and were puzzling out the phenomenon consuming the mind of a loved one. They looked to neuroscience for clarity and understanding. Some artists were personally involved with new techniques of cognitive psychotherapy. Others were inspired by the sheer physical beauty of the brain as revealed by new imaging technologies. Two of the artists explored the links between meditation, mindfulness practice and neuroscience. Issues such as the “boundary” and “binding” problems were approached, as well as the challenge of creating visual metaphors for neural processes. One artist visualized the increasing transparency of the body as researchers introduce more and more invasive technologies.